COMPOSITIONS AND METHODS FOR RESOLUTION OF INFLAMMATION - DUTTA, Anupriya; ITANO, Andrea; BODMER, Mark (2022)
Provided herein are methods and compositions related to anti-inflammatory bacteria, such as Prevotella or Veillonella parvula bacteria, for use in resolving inflammation in a subject. L'invention concerne des méthodes et des compositions associés à des bactéries anti-inflammatoires, telles que des bactériesPrevotella ou Veillonella parvula, pour une utilisation dans la résolution d'une inflammation chez un sujet.